Electrical properties of fast cooled inse single crystals - Zaslonkin, A.V.; Kovalyuk, Z.D.; Mintyanskii, I.V.; Savitskii, P.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Influence of fast cooling on electrical properties of n-InSe single crystals is investigated for an ingot grown by the Bridgman method. Electrical characteristics and their anisotropy are investigated in the temperature range 80 to 410 K. It is found that fast cooling, as soon as crystallization is completed, of the ingot leads to an increase of the free electron concentration, conductivity along layers, and conductivity anisotropy, as well as to a decrease of the Hall mobility of carriers along layers. The theoretical analysis of the mobility of carriers has shown that space-charge regions underlie the effective mechanism of their scattering.